Perlindungan Hukum Terhadap Konsumen E-Commerce dan Penyelesaian Sengketa Konsumen E-Commerce Dalam Perdagangan Produk Wanita Di Kota Pekanbaru - Desi Sommaliagustina; Yulia Fatma (LPPM Universitas Putera Batam, 2019)
ABSTRACT This research is motivated by the increasing number of people doing electronic trade. One of them is trading women's products electronically in Pekanbaru City. Electronic trading often creates obstacles such as payment procedures, legal protection, electronic signatures, and dispute resolution mechanisms that occur in the future. Electronic trading must also comply with positive law. Even though there are a number of obstacles in trading electronically, this type of trade still has an interest. Besides that ignoring technological developments will have a negative impact in the future, so that openness and proactive and anticipatory nature are alternatives that can be chosen in facing the dynamics of technological development including trade developments such as electronic commerce or commonly referred to as electronic commerce or e-commerce. This is because Indonesia has become part of the global e-commerce market. The focus of this research is 1). What is the legal protection of consumers in the trade of women's products in Pekanbaru City? 2.) What is the legal settlement if a dispute arises by the parties in the electronic trade in women's products in Pekanbaru City? The purpose of this study is to find out how the legal protection of consumers in the trade of women's products electronically in Pekanbaru City and to find out how to resolve their laws in the event of a dispute by parties in the trade of women's products electronically in Pekanbaru City. The results showed that legal instruments in Indonesia have provided legal protection to consumers even though they are not yet fully like the UUPK and the ITE Law, but there are still consumers who do not understand the UUPK and the ITE Law. And there are still consumers who do not understand their rights and obligations as consumers. The dispute resolution mechanism available is either through justice or outside the court. Keywords: Legal protection; e-commerce; dispute resolution.